A study on customer satisfaction in LIC policies with special reference to thuckalay branch - D. Sahaya Beula, Mrs.; V. P. Velmurugan, Dr (International Journal of Engineering and Technology, 2018)
Life Insurance Corporation of India is a service sector. LIC is the largest insurance Company in India. The Government of India has nationalized life insurance industry established in 1956. LIC of India with a mission to spread the message of life insurance to rural areas. The review of literature helped in understanding the characteristics of the insurance. In order to maintain customer relationship, life insurance companies should provide proper services whenever and wherever it is required. Customer Relationship Management (CRM) is one of the innovations in customer service today. Good CRM also helps to grow business and customers stay longer referrals to new customers. In the present scenario, insurance companies are facing problem of selling insurance product. These papers are covered customer satisfaction in LIC products with special reference to Thuckalay Branch. The objective of this article is to analyze the level of satisfaction among customers in Life Insurance product. This study would enable to the management to know about the level of customer satisfaction and it helps the management, to take corrective actions.Â Â